The Ediacaran frondose fossil Arborea from the Shibantan limestone of South China. (November 2020) - Wang, Xiaopeng; Pang, Ke; Chen, Zhe; Wan, Bin; Xiao, Shuhai; Zhou, Chuanming; Yuan, Xunlai
Abstract: Bituminous limestone of the Ediacaran Shibantan Member of the Dengying Formation (551–539 Ma) in the Yangtze Gorges area contains a rare carbonate-hosted Ediacara-type macrofossil assemblage. This assemblage is dominated by the tubular fossil Wutubus Chen et al., 2014 and discoidal fossils, e.g., Hiemalora Fedonkin, 1982 and Aspidella Billings, 1872, but frondose organisms such as Charnia Ford, 1958, Rangea Gürich, 1929, and Arborea Glaessner and Wade, 1966 are also present. Herein, we report four species of Arborea from the Shibantan assemblage, including the type species Arborea arborea (Glaessner in Glaessner and Daily, 1959) Glaessner and Wade, 1966, Arborea denticulata new species, and two unnamed species, Arborea sp. A and Arborea sp. B. Arborea arborea is the most abundant frond in the Shibantan assemblage. Arborea denticulata n. sp. resembles Arborea arborea in general morphology but differs in its fewer primary branches and lower length/width ratio of primary branches. Arborea sp. A and Arborea sp. B are fronds with a Hiemalora -type basal attachment. Sealing by microbial mats and authigenic cementation may have played an important role in the preservation of Arborea in the Shibantan assemblage. The Shibantan material of Arborea extends the stratigraphic, ecological, and taphonomic ranges of this genus. UUID: http://zoobank.org/554f21da-5f09-4891-9deb-cbc00c41e5f1